Compound heterozygous variants in the multiple PDZ domain protein (MPDZ) cause a case of mild non-progressive communicating hydrocephalus - Nesreen K. Al-Jezawi; Aisha M. Al-Shamsi; Jehan Suleiman; Salma Ben-Salem; Anne John; Ranjit Vijayan; Bassam R. Ali; Lihadh Al-Gazali (BMC, 2018)
Abstract Background Congenital hydrocephalus (CH) results from the accumulation of excessive amounts of cerebrospinal fluid (CSF) in the brain, often leading to severe neurological impairments. However, the adverse effects of CH can be reduced if the condition is detected and treated early. Earlier reports demonstrated that some CH cases are caused by mutations in L1CAM gene encoding the neural cell adhesion molecule L1. On the other hand, recent studies have implicated the multiple PDZ domain (MPDZ) gene in some severe forms of CH, inherited in an autosomal recessive pattern. Methods In this study, whole-exome and Sanger sequencing were performed on a 9 months old Emirati child clinically diagnosed by CH. In addition, in silico, cellular, and molecular assays have been conducted to confirm pathogenicity of the identified variants and to establish disease mechanism. Results Whole exome sequencing revealed two compound heterozygous novel variants (c.394G > A and c.1744C > G) in the affected child within the MPDZ gene. Segregation analysis revealed that each of the parents is heterozygous for one of the two variants and therefore passed that variant to their child. The outcome of the in silico and bioinformatics analyses came in line with the experimental data, suggesting that the two variants are most likely disease causing. Conclusions The compound heterozygous variants identified in this study are the most likely cause of CH in the affected child. The study further confirms MPDZ as a gene underlying some CH cases.